Effect of initial sp3 content on bonding structure evolution of amorphous carbon upon pulsed laser annealing - Xu, Naiyun (2013)
Previous work has shown that pulsed laser annealing can be used to change the bonding structure of amorphous carbon films. In this paper, the effect of initial sp3 content on bonding structure of amorphous carbon upon pulsed laser annealing was studied. Visible Raman spectroscopy was used to examine the bonding structure evolution. Here we show a detailed analysis of the Raman features—G peak position and I(D)/I(G) ratio of carbon film with initial sp3 content of 80%, 65% and 50%. The laser energy level required to induce the change of the bonding structure of carbon film decreases with the decreasing sp3 content. High resolution transmission electron microscopy (HRTEM) shows the formation of graphitic sp2 clusters form at proper laser energy. Electrical measurement also shows that the electrical property such as electrical resistivity has a close relation with the graphitic sp2 clusters.